Multidrug Resistance-Associated Protein 2 Deficiency Aggravates Estrogen-Induced Impairment of Bile Acid Metabolomics in Rats - Alaei Faradonbeh, Fatemeh; Lastuvkova, Hana; Cermanova, Jolana; Hroch, Milos; Nova, Zuzana; Uher, Martin; Hirsova, Petra; Pavek, Petr; Micuda, Stanislav (Frontiers in Physiology, 2022)
Multidrug resistance-associated protein (Mrp2) mediates biliary secretion of anionic endobiotics and xenobiotics. Genetic alteration of Mrp2 leads to conjugated hyperbilirubinemia and predisposes to the development of intrahepatic cholestasis of pregnancy (ICP), characterized by increased plasma bile acids (BAs) due to mechanisms that are incompletely understood. Therefore, this study aimed to characterize BA metabolomics during experimental Mrp2 deficiency and ICP. ICP was modeled by ethinylestradiol administration to Mrp2-deficient (TR) rats and their wild-type controls. Spectra of BAs were analyzed in plasma, bile, and stool using an advanced LC-MS method. Changes in BA-related genes and proteins were analyzed in the liver and intestine. Vehicle-administered TR rats demonstrated higher plasma BA concentrations consistent with reduced BA biliary secretion and increased BA efflux from hepatocytes to blood via upregulated Mrp3 and Mrp4 transporters. TR rats also showed a decrease in intestinal BA reabsorption due to reduced Asbt expression. Analysis of regulatory mechanisms indicated that activation of the hepatic CAR-Nrf2 pathway by accumulating bilirubin may be responsible for changes in BA metabolomics in TR rats. Ethinylestradiol administration to TR rats further increased plasma BA concentrations as a result of reduced BA uptake and increased efflux via reduced Slco1a1 and upregulated Mrp4 transporters. These results demonstrate that Mrp2-deficient organism is more sensitive to estrogen-induced cholestasis. Inherited deficiency in Mrp2 is associated with activation of Mrp3 and Mrp4 proteins, which is further accentuated by increased estrogen. Bile acid monitoring is therefore highly desirable in pregnant women with conjugated hyperbilirubinemia for early detection of intrahepatic cholestasis.